Development, Phenotypic Characterization and Genomic Analysis of a Francisella tularensis Panel for Tularemia Vaccine Testing - Bachert, Beth A.; Richardson, Joshua B.; Mlynek, Kevin D.; Klimko, Christopher P.; Toothman, Ronald G.; Fetterer, David P.; Luquette, Andrea E.; Chase, Kitty; Storrs, Jessica L.; Rogers, Ashley K.; Cote, Christopher K.; Rozak, David A.; et al. (Frontiers in Microbiology, 2021)
Francisella tularensis is one of several biothreat agents for which a licensed vaccine is needed to protect against this pathogen. To aid in the development of a vaccine protective against pneumonic tularemia, we generated and characterized a panel of F. tularensis isolates that can be used as challenge strains to assess vaccine efficacy. Our panel consists of both historical and contemporary isolates derived from clinical and environmental sources, including human, tick, and rabbit isolates. Whole genome sequencing was performed to assess the genetic diversity in comparison to the reference genome F. tularensis Schu S4. Average nucleotide identity analysis showed >99% genomic similarity across the strains in our panel, and pan-genome analysis revealed a core genome of 1,707 genes, and an accessory genome of 233 genes. Three of the strains in our panel, FRAN254 (tick-derived), FRAN255 (a type B strain), and FRAN256 (a human isolate) exhibited variation from the other strains. Moreover, we identified several unique mutations within the Francisella Pathogenicity Island across multiple strains in our panel, revealing unexpected diversity in this region. Notably, FRAN031 (Scherm) completely lacked the second pathogenicity island but retained virulence in mice. In contrast, FRAN037 (Coll) was attenuated in a murine pneumonic tularemia model and had mutations in pdpB and iglA which likely led to attenuation. All of the strains, except FRAN037, retained full virulence, indicating their effectiveness as challenge strains for future vaccine testing. Overall, we provide a well-characterized panel of virulent F. tularensis strains that can be utilized in ongoing efforts to develop an effective vaccine against pneumonic tularemia to ensure protection is achieved across a range F. tularensis strains.